The impacts of reduction in ambient fine particulate (PM2.5) air pollution on life expectancy in Taiwan - Tsai, Shang-Shyue; Chen, Chih-Cheng; Yang, Chun-Yuh (Journal of Toxicology and Environmental Health, Part A, 2022)
Fine particulate matter, particles less than 2.5 um in diameter (PM 2.5 ), is an important environmental human health factor to consider. The long- and short-term influence of PM 2.5 on health has been extensively studied in relation to many health outcomes, although few investigations examined the consequences of chronic ambient PM 2.5 on life expectancy, which constitutes an important gauge of public human health status. Therefore, the aim of this study was to investigate the effects of reducing ambient PM 2.5 levels in Taiwan on life expectancy there from 2000 to 2020. Officially reported island-wide annually average concentrations of ambient PM 2.5 , county-level life expectancies, and demographic and socioeconomic and proxy variable were collected for the prevalence of smoking from various national public agencies and organizations, since variables these might potentially confound life expectancy results. The relationship between changes in ambient PM 2.5 levels and life expectancy were determined using linear regression. Data demonstrated that counties with greater reductions in ambient PM 2.5 concentrations were associated with higher life expectancies. Adjusting for alterations in demographic and socioeconomic variables and proxy parameter, the prevalence of smoking data from a multiple regression model, it was found that a 0.3-year rise in life expectancy was noted for each 10 ug/m 3 decrease in PM 2.5 in those counties. Our findings show that reducing ambient PM 2.5 levels play an important role for prolongation of life expectancy in Taiwan.